أثر موعد الزراعة والظروف المناخية في نمو وإنتاجية بعض أصناف الثوم المنتشرة في الزراعة المحلية - الأيوبي, محمد; رعيدي, سامر; العبد الله, أسامة (Latakia University Journal -Biological Sciences Series, 2018)
أجريت الدراسة في موقعين متباينين مناخياً (الكسوة/الطيبة، سرغايا) خلال موسمين زراعيين متتاليين (2003-2004 م،2004-2005 م) واستخدم في البحث صنفان محليان من الثوم (الكسواني، اليبرودي) وصنفين مدخلين (الصيني1،الصيني2) وتمت الزراعة في 3 مواعيد (27 أيلول، 17 تشرين الأول،7 تشرين الثاني).صممت التجربة بطريقة القطع المنشقة بعاملين إذ إن الموقع هو العامل الرئيس وموعد الزراعة العامل المنشق وذلك بأربع مكررات للمعاملة الواحدة. وتبين من خلال الدراسة ما يلي: 1 – زيادة سرعة نمو وتطور نباتات أصناف الثوم المدروسة وإنتاجيتها عند الزراعة المبكرة (27 أيلول) مقارنة مع موعدي الزراعة 17 تشرين أول و7 تشرين ثاني تحت ظروف منطقتي سرغايا والطيبة. 2- إن الظروف البيئية في منطقة الطيبة أكثر ملائمة لنمو الثوم إذ انعكس ذلك إيجاباً في زيادة إنتاج الأصناف المدروسة. 3- تفوق موعد الزراعة الأول(27 أيلول) في موقع الطيبة على الموعدين الثاني والثالث بالموقع نفسه وعلى جميع المواعيد في موقع سرغايا من جهة الإنتاجية. 4- تفوق الصنفين المدخلين الصيني1 والصيني2 في إنتاجيتهما على الصنفين المحليين في كلا منطقتي الدراسة ومواعيد الزراعة. The study was conducted in two different locations with different environmental conditions (Alkisswa / Tyba, Surgaya) during two successive experimental years (2003/2004, 2004/2005). Two local varieties (Kiswany, Yebroudy) and two Chinese varieties (Chinese1, Chinese2) were used. Three planting dates were applied in this study. They were 27th September, 17th October, 7th November. The experiment design was split plots with four replications and two factors: the first is location (on main plots), the second is planting date (on sub-plots). Results showed that: 1.Earlier planting (27th September) increased growth and development of garlic plants of all varieties more than the later two dates of 17th October, 7th November under the conditions of both locations. 2.Those conditions of Tyba location are more suitable for garlic growth as they had a positive effect on the production of studiedly varieties. 3.The first planting date (27th September) in Tyba location was superior to those from the second and third dates as well as to plants from all planting dates in Surgaya location, in terms of productivity. 4.Both varieties of Chinese1 and Chinese2 were superior in their productivity the other local varieties and in both locations in all planting date.